(untitled) (translation. a transdisciplinary journal, 2021)
This study brings together three areas: language, religion, and translation; consequently, it deals with interlocking linguistic, religious, and translational research questions. Broadly speaking, in the first area, it examines linguistic representations of a particular religious experience and linguistic markers of confessional affiliation. In che second area, it focuses on religious factors conducive to certain linguistic phenomena and translational practices.